2018
DOI: 10.1002/smll.201802350
|View full text |Cite
|
Sign up to set email alerts
|

Laser‐Induced Freestanding Graphene Papers: A New Route of Scalable Fabrication with Tunable Morphologies and Properties for Multifunctional Devices and Structures

Abstract: The recently emergent laser-induced graphene (LIG) technology has endowed the fabrication of smart devices with one-step processing and scalable/designable features. Graphene paper (GP), an important architecture of 2D layered carbon, however, is never produced through LIG. Herein, a novel strategy is reported for production of freestanding GP through LIG technology. It is first determined that the unique spatial configuration of polyimide (PI) paper is critical for the preparation of GP without the appearance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
96
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 111 publications
(98 citation statements)
references
References 48 publications
2
96
0
Order By: Relevance
“…The sensor response becomes severely non-linear just before failing probably because the resistance changes abruptly due to the separation/breakage of inter-tube contacts. Similar results have been obtained in recent studies of carbon-based piezoresistive sensors [59]. The mechanical properties of GFT-implemented sensors, as shown in Figure 9d,e, improved significantly after GFT implementation, due to increased inter-tube interactions resulted from increased packing density of the buckypaper.…”
Section: Sensor Propertiessupporting
confidence: 89%
“…The sensor response becomes severely non-linear just before failing probably because the resistance changes abruptly due to the separation/breakage of inter-tube contacts. Similar results have been obtained in recent studies of carbon-based piezoresistive sensors [59]. The mechanical properties of GFT-implemented sensors, as shown in Figure 9d,e, improved significantly after GFT implementation, due to increased inter-tube interactions resulted from increased packing density of the buckypaper.…”
Section: Sensor Propertiessupporting
confidence: 89%
“…The decoration of MoS 2 significantly reduced the crack in LIG and improved the mechanical strength of the sensor. By replacing the PI film with a PI paper as the substrate for LIG synthesis, Wang et al improved the homogeneity and integrity of the LIG and demonstrated the application as a strain sensor to capture the motions of human finger and soft robot [77]. Utilizing the mechanical and acoustical performance of LIG, Tao et al fabricated a dual-functional device for physiological signals (wrist pulse and respiratory) detection, and self alarming, which offers a brand new idea for health monitoring sensors [78].…”
Section: Lig-based Mechanic Sensorsmentioning
confidence: 99%
“…In addition, the key carbon nanomaterials, such as carbon nanotubes (CNTs) and graphene, are being adopted for multiple SHM purposes for FRPs. For examples, CNTs and graphene powders have been respectively mixed in resin matrix to monitor the failures and damages of the FRPs under mechanical deformations [ 12 , 13 ]; CNT/graphene-based films [ 14 , 15 , 16 ] and papers [ 17 ] have been placed on top of or embedded between lamination layers as strain sensors for deformation detection. Graphene-coated fibers have also been utilized for monitoring tensions and/or compressions [ 18 ].…”
Section: Introductionmentioning
confidence: 99%